ANALISIS STILISTIKA DALAM KUMPULAN PUISI SAPARDI DJOKO DAMONO SEBAGAI REPRESENTASI NILAI MORAL - Yuranda, Aula; Grasela, Karin; Leniliana; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the stylistic aspects in the poetry collection of Sapardi Djoko Damono as a representation of moral values. This research uses a descriptive qualitative method with a stylistic approach focusing on diction, imagery, figurative language, and tone. The data source is a collection of Sapardi Djoko Damono’s poems, especially those reflecting daily life and emotional expression. The results show that Sapardi uses simple but meaningful diction, dominant natural imagery, and figurative language such as metaphor and personification. These stylistic elements represent moral values including sincerity, patience, love, and respect for life. Therefore, stylistic analysis proves that literary language is closely related to moral representation in poetry and can be used as a medium for character education in elementary learning.